3D-Printed Superhydrophobic and Magnetic Device That Can Self-Powered Sense A Tiny Droplet Impact. (August 2022) - Zhang, Xuan; Wang, Qi; Zou, Ruiping; Song, Bo; Yan, Chunze; Shi, Yusheng; Su, Bin
Abstract: Three-dimensional (3D)-printed magnetic soft architectures have attracted extensive attention and research from the engineering and material fields. The force-driven shape deformation of such architectures causes a change in the magnetic field distribution, indicating the capability to convert mechanical energy to electricity. Herein, we fabricate a flexible superhydrophobic and magnetic device by integrating two kinds of 3D printing approaches. The 3D-printed magnetic device (3DMD) exhibits a long-term stable mechanoelectrical conversion capacity under consecutive water droplet dripping. The output current of the 3DMD is higher than that of records in the existing literature. Combined with Maxwell numerical simulation, the mechanoelectrical conversion mechanism of the 3DMD is investigated, further guiding regulation of the diverse parameters. Moreover, three 3DMDs are integrated to light up a commercial light-emitting diode (LED) by a stream of collected rainwater. Such a combined design incorporating energy conversion is believed to promisingly motive advances in the 3D printing field.